Chorionic vascular "fit" in the human placenta: Relationship to fetoplacental outcomes. (November 2017) - Salafia, Carolyn M.; Shah, Ruchit G.; Misra, Dawn P.; Straughen, Jennifer K.; Roberts, Drucilla J.; Troxler, Larry; Morgan, Simon P.; Eucker, Barbara; Thorp, John M.
Abstract: Background: Novel measures of the chorionic plate and vessels are used to test the hypothesis that variation in placental structure is correlated with reduced birth weight (BW) independent of placental weight (PW), suggesting functionally compromised placentas. Methods: 916 mothers recruited to the Pregnancy, Infection and Nutrition Study delivering singleton live born infants at >30 gestational weeks had placentas collected, digitally photographed and weighed prior to formalin fixation. The fetal-placental weight ratio (FPR) was calculated as birthweight/placental weight. Beta (beta) was calculated as ln(PW)/ln(BW). Chorionic disk perimeter was traced and chorionic surface shape (CS) area was calculated. "Fit" was defined as the ratio of the area of the vascular to the full chorionic surface area. The sites at which chorionic vessels dived beneath the chorionic surface were marked to calculate the chorionic surface vessel (CV) area. The centroids of shapes, the distance between centroids and other measures of shape irregularities were calculated. Principal components analysis (PCA) created three independent factors. Factors were used in regression analyses to explore relations to birth weight, trimmed placental weight, FPR, and beta. Specific measures of shape irregularity were also examined in regression analyses for interrelationships and to predict birth weight, placental weight, FPR, and beta. Results: Variables related to disk size (CS area, perimeter) were correlated with BW, GA, trimmed PW and beta. "Fit" (the ratio of CV area to CS area), measures of shape irregularities, and the distance between the cord insertion and the centroids of surface and vascular areas were also correlated with one or more of the clinical outcome variables. PCA yielded three factors that had independent effects on birth weight, placental weight, the fetal-placental weight ratio, and beta (each p < 0.0001). Addition of GA did not alter the factors' associations with outcomes. Chorionic "fit" (ratio of areas), also included within the factor analysis, was a positive predictor of birth weight (p = 0.005) and FPR (p = 0.002) and a negative predictor of beta (p = 0.01). Fit was statistically significantly associated with greater distances between the umbilical cord insertion site and the CS (p < 0.001) and CV centroids (p < 0.001), and to lesser displacement between CS and CV centroids (p < 0.001). Conclusions: Measures of CS and CV account for variation in placental efficiency defined by beta, independent of GA. Macroscopic placenta measurements can identify suboptimal placental development. Highlights: Chronic vessel area, surface shape, and umbilical cord "off-centeredness" account for birth and placental weight variance. Novel measures of these areas and their centroids provide insights in differences in birth and placental weights, and placental efficiency as quantified by beta. These measures could be captured as a shape of Doppler color and analyzed, as a potential marker of preclinical fetal jeopardy.